Efektivitas Pendidikan Kesehatan Terhadap Perilaku Cuci Tangan Pakai Sabun Dalam Upaya Pencegahan Covid-19 - Adriani, Adriani; Oktavia, Sisi; Febrina, Wiwit (REAL in Nursing Journal, 2021)
Background: Covid-19 causes respiratory problems and inflammation of the lungs. This disease is caused by a viral infection. The implementation of hand washing with soap carried out in elementary schools for the prevention of Covid-19 has not been carried out properly because the UKS program is not running optimally and has not received health education. This study aims to determine the effectiveness of health education on the knowledge and actions of washing hands with soap in an effort to prevent Covid-19 in elementary schools. Methods: This research was analytical descriptive research with Quasi Experiment approach with One Group Pre-test and Post-test design. A sample of 20 students using total sampling of students in grades V and VI, data processing using non-parametric tests (Wilcoxon and Paired T test). Results: The results showed that the average knowledge of students before the intervention was 6.15 and the average knowledge after the intervention was 6.9 with p value = 0.003, the average action before the intervention was 2.65, the average after the intervention was 4.6 with p value = 0.000. Conclusion: Based on the results of the study, it was concluded that health education was effective in the knowledge and actions of washing hands with soap as an effort to prevent Covid-19 in elementary schools. It is hoped that the health education method can be used in health education programs for students' knowledge and actions in an effort to prevent Covid-19. Keywords: Covid-19, Health Education, Knowledge, Skills